Geodetic observation and modelling of continental deformation in Iran and Turkey - Walters, RJ (2012)
In this thesis I use Interferometric Synthetic Aperture Radar (InSAR) and GPS geodetic observations, along with numerical models, to examine the distribution of strain, assess seismic hazard, and study the dynamics of deformation across Turkey and Iran. I measure interseismic strain accumulation across the Ashkabad fault using InSAR, and find that atmospheric corrections using MERIS (Medium Resolution Imaging Spectrometer) data are necessary in order to retrieve the tectonic signal in the presence of large atmospheric delays. I estimate a slip rate of 5-12 mm/yr for the Ashkabad fault which is faster than previous geodetic estimates. I also attempt to validate atmospheric corrections derived from the ERA-Interim numerical weather model and find that they do not work satisfactorily for this region. I produce InSAR-derived velocity maps for five overlapping tracks in Eastern Turkey, covering both the North Anatolian Fault (NAF) and East Anatolian Fault (EAF), and measure slip rates for the NAF and EAF of 20+/-3 mm/yr and 10+/-2 mm/yr respectively. I calculate a velocity field for Eastern Turkey from these InSAR data and a compilation of GPS data, and find that strain is mainly localised across the NAF and EAF and that there is negligible differential vertical motion across the Anatolian Plateau. I construct a thin viscous sheet model for Iran and find that the GPS velocity field is well described by deformation of a ductile lithosphere. Contrary to previous suggestions, a rigid central Iran is not required to match the kinematics of Iranian deformation, but buoyancy forces acting in the lithosphere are found to play an important role. I develop a new method to assess slip rates and therefore seismic hazard on major faults in Iran from this continuum model. In this thesis I have measured slip rates across three major strike-slip faults using InSAR; the first time this has been achieved for the Ashkabad fault and the EAF. I have demonstrated the importance of atmospheric correction for these results, and have shown that Iran deforms as a continuous medium.